AB1160 Golimumab in 25 young adults affected by juvenile idiopathic arthritis (JIA) non responders to other biological agents: Preliminary data. (23rd January 2014) - Pontikaki, I.; Gattinara, M.; Donati, C.; Meroni, P.L.; Gerloni, V.
Abstract : Background: Biological agents licensed in JIA have demonstrated a favourable benefit-to-risk profile. Nevertheless, intolerance, loss and lack of efficacy or adverse events have led to try other therapeutic options. Objectives: To evaluate efficacy and safety of Golimumab in young adults affected by JIA with active polyarthritis (with or without uveitis), non responders to MTX, antiCD20 and anti-IL-1 and intolerant to the first generation of antiTNF (Infliximab, Etanercept and Adalimumab). Methods: In our Centre, since november '99 to dicembre 2011, 288 patients affected by refractory JIA were treated with TNF inhibitors and since May 2011, 25 patients (16 F, 9 M) affected by refractory JIA, non responders to other biologic agents, were enrolled in Golimumab (Simponi). Patients had failed MTX as monotherapy, previous TNF inhibitors, Rituximab and anti-IL1 therapy. Two patients had been treated with 8 different biologic agents, 1 patient with 7, 2 patients with 6, 5 patients with 5, 3 with 3, 7 with 2 and 3 patients with just one previous biologic agent. Two patients had a Systemic onset of JIA, 4 polyarthritis RF negative, 3 enthesitis related arthritis, 1 psoriatic arthritis, 6 oligoarthritis persistent and 9 oligoarthritis extended. Median age was of 28.7 years, median onset age 7.3 years, median disease duration 19.8 years. All patients had active disease, 8 patients had a previous history of chronic Iridocyclitis. Patients received Golimumab at the dose of 50 mg subcutaneously every month, as in RA. Fifteen patients receive Golimumab in association with MTX. Results: All patients were evaluated according to EULAR criteria (DAS 28). Seventeen patients (68%) were responders, 5 patients were not evaluable because of follow-up and 3 patients were non responders (1 of these 3 pts droped-out). No adverse events were observed. No adverse events were occured. Conclusions: Golimumab seems to be efficacious and well tolerated and it could be a good treatment of long lasting refractory JIA in young adults who failed other biologics. These data seem to be one of the first experiences in the use of Golimumab in young adults affected by JIA. Disclosure of Interest: None Declared